Pengaruh Pengasuhan “Mbah” Terhadap Perilaku dan Prestasi Belajar Anak di MTsN 16 Jombang - Suwarso (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
Parenting is related to behavior and learning achievement, where parenting is one of the factors that influence children's behavior and learning achievement. The aim of the study was to find out and analyze the effect of mbah parenting on children's behavior and learning achievement at MTsN 16 Jombang and to find out and analyze the extent to which mbah parenting influences children's behavior and learning achievement. This research method uses quantitative correlational ex post facto. Population and sample 63 students. Based on the results of data processing between grandparents' parenting on children's behavior and learning achievement, it is known that both Asymp Sig. (2-tailed) is worth 0.000. because the value is 0.000 ≤ 0.05, it can be concluded that there is a significant relationship between "grandfather" parenting on children's behavior, and there is a significant relationship between "grandmother" parenting on children's learning achievements